- Mediastinopleurotomy in the diagnosis of C.B.P. - Bertullo, Hugo; Chifflet, Juan; Domínguez, Carlos; Bogliaccini, Gustavo; Pomi, Jorge (Cirugía del Uruguay, 1982)
45 mediastinopleurotomies were evaluate. A brief historical outline is done. In lung cancer it has only diagnostic indications. 39 were used as a diagnostic tool and 6 for staging. This procedure is useful in high risk patients and it should be chosen instead of exploratory thoracotomy in those patients who have an inoperable cancer.